PENERAPAN MULTIMEDIA ARTICULATE STORYLINE BERBASIS MODEL THINK TALK WRITE TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR DI KELAS V - FITRIYANI, FITRIYANI; Yuwono, Agus; Purwati, Panca Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the lack of use of innovative learning media in learning procedure text writing skills. The skill of writing procedure text is the skill in arranging the steps of doing something sequentially to achieve a certain goal. Think Talk Write model is a cooperative learning model that integrates the process of thinking, discussing, and writing gradually. The purpose of this study is to describe the process of implementing the Think Talk Write model and the effectiveness of the application of Articulate Storyline multimedia on the skills of writing procedure texts in Class V. The research method used mixed methods with concurrent embedded model (quantitative and qualitative). The research subjects were 22 Class V students. Data collection techniques used questionnaires and observation. The data analysis technique used quantitative-descriptive. The results showed that the average pre-test score of procedure text writing skills of 70,83 increased in the post-test of 79.92 with a percentage of completeness of 90.91%. Based on the results of the study, it is concluded that the Multimedia Articulate Storyline based on the Think Talk Write Model is very well completed to improve students' procedure text writing skills in Class V.